Child-Centered User Interface Design for Early Language Learning Applications: A Qualitative Comparative Study - Fenie Fedora Wijaya; Shienny Megawati Sutanto (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Background: In the digital learning era, user interface (UI) design plays an important role in shaping how children engage with educational applications, particularly in early language learning contexts. however, many applications are not fully aligned with children’s cognitive, emotional, and developmental needs. Objective: This study aims to examine how UI design in child-centered language learning applications can be optimized to support children’s cognitive and emotional needs while enhancing learning outcomes. Method: This study adopts a qualitative comparative approach, integrating a literature review, visual analysis of two English-language learning applications (Duolingo ABC and BOOKR Class), semi-structured interviews with three design experts, and focus group discussions with six children aged 5–8. Data were collected through observation, expert validation, and user interaction, and analyzed using thematic analysis. Results: The findings indicate that intuitive, minimal-step navigation reduces cognitive load and supports task completion; balanced color strategies sustain attention without overstimulation; large sans-serif typography improves reading accuracy; and expressive mascots enhance emotional engagement. However, children’s preferences vary across developmental stages, highlighting the need for adaptive rather than standardized design approaches. Conclusion: UI design functions as a pedagogical mediator that influences comprehension, engagement, and early literacy development. The study proposes a child-centered guideline integrating cognitive simplicity, emotional resonance, and context- ensitive design decisions, contributing to educational technology by demonstrating how developmentally aligned interface design can improve both usability and learning effectiveness.